Dubai: Stadt der Attraktionen. "Image"-Bildung in Architektur und Stadtplanung. - Krämer, Steffen (KIT Scientific Publishing, 2014)
Since the last two decades the city of Dubai permanently comes under fire of international criticism. But the objections mostly refer to political or social defects, and not to the specific urban shape of the city. However, architecture and new urbanism of Dubai show a whole string of innovative formal principles, which can be used for international town planning in future. "Image" is the basic concept to create not only iconic buildings, but new spatial structures, dominated by architectural prospects, axial perspectives or dramatic configurations. Instead of the old grid system in modern town planning new districts of Dubai show remarkable compositions in different clusters of skyscrapers. For that reason "Learning from Dubai" can be a useful strategy in contemporary urbanism.
Keywords: Stadtplanung; Architektur; Städtebau; Stadtbild; Stadtgestaltung